The Effect of Snake and Ladder Game on Students’ Speaking Skill - Sholikatin, Ana Arifa; Sofiana, Nina (Universitas Sebelas Maret, 2025)
Fourth-grade students at SDN 01 Purwogondo struggle with English speaking skills, especially vocabulary and pronunciation, due to limited confidence, low motivation, and monotonous teaching methods lacking engaging media. The purpose of this study was to determine the use and effect of snakes and ladders game activities on students' speaking skills. This study investigated at SDN 01 Purwogondo in Grade IV totaling 30 students. This study used a quantitative research design using a pre-test and post-test. Speaking performance was evaluated based on vocabulary, fluency, pronunciation, and comprehension. The results showed a significant increase in students' speaking skills, with an average pre-test score of 66.2 and a post-test score rising to 92.9. The results of the paired sample t-test calculation with a sign (2 tails) the result was .000, lower than 0.05 as a significance level. The results of the analysis obtained a p-value of 0.000, so H0 was rejected and H1 was accepted, and the results of the hypothesis showed that there was a significant increase in students' speaking skills after using the snakes and ladders game. Siswa kelas empat di SDN 01 Purwogondo mengalami kesulitan dalam keterampilan berbicara bahasa Inggris, terutama dalam hal kosakata dan pelafalan, akibat kurangnya kepercayaan diri, motivasi yang rendah, dan metode pengajaran yang monoton tanpa media yang menarik. Tujuan dari penelitian ini adalah untuk menentukan penggunaan dan pengaruh aktivitas permainan ular tangga terhadap keterampilan berbicara siswa. Penelitian ini menyelidiki di SDN 01 Purwogondo pada Kelas IV yang berjumlah 30 siswa. Penelitian ini menggunakan desain penelitian kuantitatif dengan menggunakan pre-test dan post-test. Kinerja berbicara dievaluasi berdasarkan kosakata, kelancaran, pengucapan, dan pemahaman. Hasilnya menunjukkan peningkatan yang signifikan dalam keterampilan berbicara siswa, dengan skor rata-rata pra-tes menjadi 66,2 dan skor pasca-tes naik menjadi 92,9. Hasil perhitungan uji-t sampel berpasangan dengan tanda (2 ekor) hasilnya adalah .000, lebih rendah dari 0,05 sebagai tingkat signifikansi. Hasil analisis memperoleh nilai p sebesar 0,000, jadi H0 ditolak dan H1 diterima, dan hasil hipotesis menunjukkan bahwa ada peningkatan yang signifikan dalam keterampilan berbicara siswa setelah menggunakan permainan ular tangga.